Geochemical portray of the Pacific Ridge: New isotopic data and statistical techniques - Hamelin, Cedric; Dosso, Laure; Hanan, Barry B.; Moreira, Manuel; Kositsky, Andrew P.; Thomas, Marion Y. (Earth and Planetary Science Letters, 2011)
Samples collected during the PACANTARCTIC 2 cruise fill a sampling gap from 53 degrees to 41 degrees S along the Pacific Antarctic Ridge (PAR). Analysis of Sr, Nd, Pb, Hf, and He isotope compositions of these new samples is shown together with published data from 66 degrees S to 53 degrees S and from the EPR. The recent advance in analytical mass spectrometry techniques generates a spectacular increase in the number of multidimensional isotopic data for oceanic basalts. Working with such multidimensional datasets generates a new approach for the data interpretation, preferably based on statistical analysis techniques. Principal Component Analysis (PCA) is a powerful mathematical tool to study this type of datasets. The purpose of PCA is to reduce the number of dimensions by keeping only those characteristics that contribute most to its variance. Using this technique, it becomes possible to have a statistical picture of the geochemical variations along the entire Pacific Ridge from 70 degrees S to 10 degrees S. The incomplete sampling of the ridge led previously to the identification of a large-scale division of the south Pacific mantle at the latitude of Easter Island. The PCA method applied here to the completed dataset reveals a different geochemical profile. Along the Pacific Ridge, a large-scale bell-shaped variation with an extremum at about 38 degrees S of latitude is interpreted as a progressive change in the geochemical characteristics of the depleted matrix of the mantle. This Pacific Isotopic Bump (PIB) is also noticeable in the He isotopic ratio along-axis variation. The linear correlation observed between He and heavy radiogenic isotopes, together with the result of the PCA calculation, suggests that the large-scale variation is unrelated to the plume-ridge interactions in the area and should rather be attributed to the partial melting of a marble-cake assemblage. (C) 2010 Elsevier B.V. All rights reserved.